Early Functional Treatment and Modern Cast Making for Indications in Hand Surgery - S. Bohr; N. Pallua (Advances in Orthopedics)
Cast treatment can serve both as a nonsurgical treatment option and as a means for providing postoperative protection. However, with the duration of immobilization intervals, the benefits of cast treatment, especially in hand surgery, are at risk of being outweighed by undesired drawbacks such as joint stiffening and contracture formation. In order to minimize potential complications commonly associated with cast treatment, efforts to further improve cast making must attempt to reconcile two conflicting objectives: (1) to achieve stability and rigidity at the site of injury (e.g., fracture retention) and (2) to allow free range of joint movement as early as possible. In addition, in order to assure patient compliance, modern cast treatments should aim to improve wearing-comfort of the cast. This paper describes modern cast designs for four common types hand injuries, with sample cases highlighting the clinical outcome of each treatment.